ANALISA STABILITAS KETAHANAN DAN KEAMANAN DINDING PENAHAN TANAH PADA SUNGAI SEDAPAT TALANG BULUH KECAMATAN TALANG KELAPA KABUPATEN BANYUASIN - Anderson, Ganda; Saputro, M. Elan; Setiawan, Ari (Universitas Muhammadiyah Palembang, 2023)
Soil Retaining Wall is one of the constructions used to hold the soil or provide stability to the soil that has different heights. Soil retaining wall function to support the soil as well prevent it from the danger of landslides, so it does not experience landslides both due to the load of rainwater, the weight of the soil itself, or as a result of the load acting on it. Based on the way to achieve stability, the soil retaining wall can be classified into several types, namely gravity wall, cantilever wall, counterfort wall, buttress wall. In this research, we plan gravity-type soil retaining wall. Planning this gravity-type soil retaining wall is considered necessary because in today's competitive era, in addition to accuracy and accuracy in planning, speed in calculating is also needed. Therefore, using this program is expected to increase competitiveness for planners, especially planning related to soil retaining walls.